The Fe-Zn Isotopic Characteristics and Fractionation Models: Implications for the Genesis of the Zhaxikang Sb-Pb-Zn-Ag Deposit in Southern Tibet - Da Wang; Youye Zheng; Ryan Mathur; Song Wu (Geofluids)
The genesis of the Zhaxikang Sb-Pb-Zn-Ag deposit remains controversial. Three different geological environments have been proposed to model mineralization: a hot spring, a magmatic-hydrothermal fluid, and a sedimentary exhalative (SEDEX) overprinted by a hot spring. Here, we present the electron probe microanalysis (EPMA) and Fe-Zn isotopic data (microsampled) of four samples from the first pulse of mineralization that show annular textures to constrain ore genesis. The Zn/Cd ratios from the EPMA data of sphalerite range from 296 to 399 and overlap the range of exhalative systems. The δ56Fe values of Mn-Fe carbonate and δ66Zn values of sphalerite gradually decrease from early to late stages in three samples. A combination of the EPMA and isotopic data shows the Fe-Zn contents also have different correlations with δ66Zn values in sphalerite from these samples. Rayleigh distillation models this isotope and concentration data with the cause of fractionation related to vapour-liquid partitioning and mineral precipitation. In order to verify this Rayleigh distillation model, we combine our Fe-Zn isotopic data with those from previous studies to establish 12 Fe-Zn isotopic fractionation models. These fractionation models indicate the δ56Fei and δ66Zni values (initial Fe-Zn isotopic compositions) of the ore-forming system are in the range of -0.5‰​​ ~−1‰ and -0.28‰​ ~0‰, respectively. To conclude, the EPMA data, Fe-Zn isotopic characteristics, and fractionation models support the SEDEX model for the first pulse of mineralization.